O futuro entre o rural e o urbano: um estudo de caso sobre a juventude rural no Município de Morro Redondo-RS. - Costa, Maria Regina Caetano (2011)
The rural population has experienced changes in terms of occupation of its workforce and, mainly, in their conditions of income earning. These changes affect differently the diverse sectors of this population. Among the family farmers have been occurring an important process of rural areas abandonment, especially by the young, who search in the urban environment the accomplishment for their life projects. The youth, who identified in the agricultural activity a fertile field for their professional achievement, began to realize other activities unrelated to agriculture. The reproductive strategies of rural families eventually are adapted to the socioeconomic context in which they live. One can also observe that the likely crises and changes in rural areas affect the construction of the projects of the rural youth, then they start to reformulate the familiar or individual strategies, in distinct social and economic contexts. This study is characterized as a sequence of a research work that originated a dissertation defended at the Universidade Federal de Pelotas in 2006, whose target audience were high school students from the School Nosso Senhor do Bonfim, in the urban perimeter of Morro Redondo, RS, Brazil. Facing this scenery we intended, through a case study, to return to these these young people in order to investigate which are the professional strategies that have been adopted by the rural youth for the permanence or desertion of the area in the municipality of Morro Redondo city, RS. To evaluate the current information and the information obtained in the earlier period, we used qualitative and quantitative methodology combined, in order to cross the produced speeches. The interviews allowed us to conclude that the uncertainty of a fixed payment is manifested as an element that contributes to the youth to the abandon the familiar activity and the continuity of the formal education has shown itself as strategy to achieve their life projects, thus threatening the possibility of succession in family production units.